2003
DOI: 10.1080/00365510310000420
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical values in persons older than 82 years of age: report from a population‐based study of twins

Abstract: According to international standards, reference values for biochemical tests should be obtained in disease-free subjects and for therapies that may influence measurement values. For elderly persons, especially the very old, such a requirement is difficult to meet, since few of these individuals are free of ongoing or former diseases. The present study of a population-based Swedish twin sample comprises 535 individuals (186 males, 349 females) who were at least 82 years of age at blood sampling. Survival over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…16 The biochemical values were consistent with published reference values for the elderly. 17,18 substances, all of which are associated with increased risks for cardiovascular disease and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…16 The biochemical values were consistent with published reference values for the elderly. 17,18 substances, all of which are associated with increased risks for cardiovascular disease and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the close correlation between Hcy, low vitamin B 12 , and low folate levels, the latter two were not associated with an increased mortality rate. High Hcy levels have been associated with risk for ischemic stroke, (46) dementia, (9) and mortality risk, (47) but decreasing Hcy levels (high-dose treatment with vitamin B 6 , B 12 , and folic acid) did not decrease the risk for ischemic stroke, coronary heart disease, or death in a recent study. (46) However, Sato et al (14) showed a reduction in number of hip fractures with vitamin B 12 and folate treatment compared with placebo in a high fracture risk group-stroke patients.…”
Section: Figmentioning
confidence: 92%
“…They may also change as a result of variation in techniques used by different laboratories [26–28]. The parameters can also vary following pathological conditions that affect major body organs and systems that produce, secrete, or store them such as the liver, pancreas, kidney, bone marrow, and the immune system [2931]. In clinical chemistry, reference values are commonly based on reference of the Western population; these usually do not match with the Indian population.…”
Section: Introductionmentioning
confidence: 99%